IN VITRO ANTHELMINTIC ACTIVITY OF AQUEOUS AND METHANOLIC EXTRACTS OF Guiera senegalensis AGAINST FOUR SPECIES OF TRICHOSTRONGYLID NEMATODES - GAGMAN, HALADU ALI; AHMAD, HAMDAN; IZZAUDIN NIKHIM, NIK AHMAD IRWAN (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
Gastrointestinal nematodes increasing resistance to synthetic drugs and the side effects of the drugs as it interferes with the quality of animal products call for a search of alternative anthelmintic from plants. This research evaluates the anthelmintic potential of methanol and aqueous extracts of G. senegalensis against the migration of H. contortus, T. colubriformis, O. circumcincta and Oesophagostomum spp. Each of the species was incubated in 0.2, 0.4, 0.6, 0.8, 1.0, and 2.0 mg/ml of aqueous and methanol extracts of G. senegalensis and later transferred to migratory plates. Larvae in the positive control were treated with 0.02 μg/ml of ivermectin while those in the negative control were treated with M9. Both methanol and aqueous extracts exhibited good larvicidal activities against the migration of all the species of the nematodes. However, the efficacy of methanol extract was higher than aqueous extract in every tested species (P < 0.05). The most sensitive of all the species to the extracts was H. contortus which recorded the lowest IC50 values of 0.631 and 0.350 mg/ml for aqueous and methanol extract respectively. The less sensitive of all the species was Oesophagostomum spp as it recorded the highest IC50 values of 0.840 and 0.535 mg/ml for aqueous and methanol extracts respectively. Ivermectin was more efficient that the plant extracts.